Brain Kynurenine Pathway Metabolite Levels May Reflect Extent of Neuroinflammation in ALS, FTD and Early Onset AD - Annelies Heylen; Yannick Vermeiren; Ido P. Kema; Martijn van Faassen; Claude van der Ley; Debby Van Dam; Peter P. De Deyn (MDPI AG, 2023)
Objectives: Despite distinct clinical profiles, amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) patients share a remarkable portion of pathological features, with a substantial percentage of patients displaying a mixed disease phenotype. Kynurenine metabolism seems to play a role in dementia-associated neuroinflammation and has been linked to both diseases. We aimed to explore dissimilarities in kynurenine pathway metabolites in these early onset neurodegenerative disorders in a brain-region-specific manner. Methods: Using liquid chromatography mass spectrometry (LC-MS/MS), kynurenine metabolite levels were determined in the brain samples of 98 healthy control subjects (n = 20) and patients with early onset Alzheimer's disease (EOAD) (n = 23), ALS (n = 20), FTD (n = 24) or a mixed FTD-ALS (n = 11) disease profile. Results: Overall, the kynurenine pathway metabolite levels were significantly lower in patients with ALS compared to FTD, EOAD and control subjects in the frontal cortex, substantia nigra, hippocampus and neostriatum. Anthranilic acid levels and kynurenine-to-tryptophan ratios were consistently lower in all investigated brain regions in ALS compared to the other diagnostic groups. Conclusions: These results suggest that the contribution of kynurenine metabolism in neuroinflammation is lower in ALS than in FTD or EOAD and may also be traced back to differences in the age of onset between these disorders. Further research is necessary to confirm the potential of the kynurenine system as a therapeutic target in these early onset neurodegenerative disorders.